Strategies for Developing an Adaptive Curriculum to Address Social and Technological Challenges for Improving Education Quality - Indah Dwi Cahyani; Hafizo; M. Mawardi; Riyanti; Abdurrahmansyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study examines strategies for developing an adaptive curriculum that responds to social and technological challenges in Indonesia. This qualitative research employed a systematic literature review method by analyzing scientific articles and educational policy documents. The population consisted of relevant articles and policies selected through strict criteria, with a sample of 20 journals. The analysis technique used thematic content analysis. The findings reveal several key strategies: participatory and flexible curriculum management, the development of inclusive curricula for special needs and cultural diversity, and the integration of AI-based adaptive learning technologies. The challenges include limited infrastructure, low digital literacy among teachers, resistance to change, and issues related to data ethics. The conclusion emphasizes that effective collaboration among schools, the government, and industry is essential for bridging educational gaps and aligning the curriculum with the needs of the modern workforce. Future research is recommended to include empirical validation and practical applications.